Board gender diversity and capital structure: Evidence from the Portuguese listed firms - Teodosio, Joao; Lisboa, Ines; Oliveira, Celia (International Journal of Applied Economics, Finance and Accounting, 2023)
This investigation analyzes the impact of board gender diversity on the financial policies of non-financial Portuguese listed firms between 2010-2019. The study applies the two-step Generalized Method of Moments (GMM) for econometric analysis. The results show that board gender diversity affects firms’ capital structure. While female directors have no determinant role in defining firm indebtedness levels, they significantly contribute to its structure. Our results demonstrate that female directors, particularly those with executive roles, consistently contribute to reducing firms’ long-term debt and prefer to issue short-term debt. Moreover, female directors tend to manage trade over financial debt, especially in older firms. Independent female directors play a significant role in smaller firms by decreasing long-term and financial debt. The study supports the notion that gender diversity on the board contributes differently to the firms’ financial policies. Additionally, the findings are in line with the assumptions of agency, resource dependence, and pecking order theories. This study shows that gender diversity promotes short-term debt as a substitute for bank loans to avoid increasing firms’ risk, which ultimately impacts the definition of financial debt levels.